INOVASI PEMBELAJARAN AKIDAH AKHLAK ABAD 21 DENGAN METODE MULTIPLE INTELEGENCES - Saibah Saibah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2021)
Education in the 21 century requires educators to be more creative, but there are still many educators who use monotonous learning methods so that students tend to get bored and ignore learning. Purpose of this study was to determine the effectiveness of the use of multiple intelligence learning methods when applied in learning Akidah Akhlak. This study uses a qualitative research method with a phenemonological approach. The phenemonological approach used is the Schutz approach. Data analysis is an inductive analysis. The subjects that became the focus of this study were the Akidah Akhlak education teachers, seventh grade students of SMP Muhammadiyah one Jember. The results of the research of the Multiple Intelligences method are effective in learning because it can provide learning motivation to students and are able to hone the intelligence of each student.